1999
DOI: 10.1007/s007010050326
|View full text |Cite
|
Sign up to set email alerts
|

Premeatal and Retromeatal Cerebellopontine Angle Meningioma. Two Distinct Clinical Entities

Abstract: The topological classification of CPA-meningiomas according to their location anterior or posterior to the ICA is important, because the clinical presentation, the surgical strategy to be applied, and the functional outcome of critical neural structures differ between the two subtypes. Our results provide substantial evidence for the paradoxical observation that premeatal meningiomas have a significantly worse postoperative functional outcome compared to retromeatal meningiomas although premeatal meningiomas b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 11 publications
1
47
0
16
Order By: Relevance
“…They only displace, but do not infi ltrate the facial-cochlear nerve complex. As described by us earlier (Schaller 2003a , b ;Schaller et al 1999a ), the Vth cranial nerve was frequently displaced to the superior surface of the tumour, and the lower cranial nerves (IX-XI) were often distorted towards the foramen magnum. For these reasons, auditory and facial nerve function were found to be preserved postoperatively.…”
Section: Retromeatal Tumor Locationmentioning
confidence: 87%
See 3 more Smart Citations
“…They only displace, but do not infi ltrate the facial-cochlear nerve complex. As described by us earlier (Schaller 2003a , b ;Schaller et al 1999a ), the Vth cranial nerve was frequently displaced to the superior surface of the tumour, and the lower cranial nerves (IX-XI) were often distorted towards the foramen magnum. For these reasons, auditory and facial nerve function were found to be preserved postoperatively.…”
Section: Retromeatal Tumor Locationmentioning
confidence: 87%
“…Some CPA meningiomas may remain asymptomatic for a patient's lifetime or be detected incidentally when a patient has a neuroimaging for unrelated symptoms. Symptoms are typically present a mean of 2.5-5 years before the actual diagnosis (Schaller et al 1995(Schaller et al , 1999a. The presenting signs and symptoms depend on the size and location/extent of the tumor as described earlier here and can be related to brainstem compression, cerebellar compression, cranial nerve involvement as well as increased intracranial pressure caused by mass effect or hydrocephalus (Schaller et al 1995(Schaller et al , 1999a.…”
Section: Symptomsmentioning
confidence: 95%
See 2 more Smart Citations
“…They found the clinical manifestations were different between these two types. 18 According to the dural attachment of the meningioma, Schaller et al 7 divided them into premeatal and retromeatal meningiomas, and showed that premeatal meningiomas have a significantly worse post-operative functional outcome than retromeatal meningiomas, although premeatal meningiomas became symptomatic earlier and had smaller sizes. Desgeorges et al 19 classified the posterior surface of the petrous bone into three equal zones according to imaging manifestation: 19 Voss et al 4 classified posterior petrous meningiomas into four types: retromeatal, premeatal, suprameatal and inframeatal.…”
Section: Discussionmentioning
confidence: 99%